Assessing the Gap between Observed and Perceived Inflation in the Euro Area: Is the Credibility of the HICP at Stake? - Luc Aucremanne; Marianne Collin; Thomas Stragier (National Bank of Belgium, 2007)
We find strong econometric support for a break in the relationship between perceived and HICP inflation in the euro area, triggered by the introduction of euro notes and coins in January 2002. The break is fairly homogeneous across individuals with different socio-economic characteristics. We found no support for the thesis according to which perceptions are systematically formed by frequently purchased products. A similar break is found when national CPIs instead of HICPs are used as benchmarks. The role of the non-inclusion of owner-occupied housing in the HICP was negligible. Therefore the credibility of the HICP per se is not at stake.
Keywords: C22; C23; D12; E31; 330; inflation; perceived inflation; panel unit roots tests; Inflation; Wirtschaftspsychologie; Eurozone; EU-Staaten